Validation of the Thai Version of the Marital Commitment Scale (MCS) - Tanchotsrinon, Pornsawan; Maneesri, Kakanang (Journal of Population and Social Studies [JPSS], 2017)
The Marital Commitment Scale (MCS) developed by Johnson, Caughlin, and Huston (1999) is a widely-used instrument for assessing relationship commitment in a population. Although this scale has been used in the United States, there has been no study on its applicability in Asia. Therefore, this study developed a Thai version of the MCS (MCS-Thai) and recruited 394 adults in Thailand as sample. The validity and reliability of the MCS-Thai were examined and found to be compatible with the original version. The results of Confirmatory Factor Analysis indicated that three-factor structure (personal, moral, and structural commitment) to study relationship commitment was compatible with the conceptualization of marital commitment in the US and Thailand. However, the homogeneity of the sample (married individuals) limits the generalizability of these findings.